Framework of study on Tourist Route and its Implication towards Island Tourism Development in Malaysia - S.M. Hashemia, S.M. Hashemia; Jusoh, Jamil (School of Social Sciences, 2015)
In Malaysia nowadays, route tourism is becoming positively developed, including connecting with each other the tourism resources of a number of smaller locations and marketing them jointly as an individual tourism destination area. Tourists destinations are in a condition of constant modify. This particular advancement is more extreme in the case of Island destinations due to their geographic restrictions. This research is a framework of the top concern areas for tourism development in Malaysia.